Dissociating the roles of alpha oscillation sub-bands in visual working memory - Na Zhao; Qiang Liu (NeuroImage)
Alpha oscillations play a critical role in visual working memory (VWM), but the specific contributions of lower and upper alpha sub-bands remain unclear. To address this, we employed a whole-field change detection paradigm to investigate how alpha power modulation and decoding accuracy differ between these sub-bands in response to varying set sizes and spatial extents of memory arrays. Our results revealed that lower alpha (8–9 Hz) exhibits widespread event-related desynchronization (ERD) during the early maintenance phase, which increases with set size and reflects attentional allocation to individual memory items. In contrast, upper alpha (10–12 Hz) demonstrates posteriorly localized ERD that is strongly associated with the spatial extent of memory arrays. During the late maintenance phase, upper alpha transitions to event-related synchronization (ERS), suggesting a role in suppression of irrelevant sensory inputs and enhancement of alertness. Multivariate decoding analyses showed that all alpha sub-bands accurately decoded both set size and spatial extent across time windows, with lower alpha achieving better decoding performance during the early maintenance phase and upper alpha excelling in later stages. These findings suggest that alpha oscillations encode both the number and spatial distribution of memory items, with lower and upper alpha sub-bands serving complementary roles in encoding and maintaining VWM representations.